Tip-cylinder electrode plasma to enhance the coating of conductive yarn process - Valentinus Galih Vidia Putra; Lutfi Zulfikar; Atin Sumihartanti; Juliany Ningsih Mohamad; Yusril yusuf (Jurnal Rekayasa Proses, 2020)
This study aims to develop conductive textile materials using a polyester textile yarn by applying a knife coating method and pre-treatment of a tip-cylinder plasma electrode. In this research, carbon ink was coated on polyester staple yarn which was given a pre-treatment with a plasma generator and coated with the knife coating method. The electrical conductivity of conductive yarns produced from this study was divided into two types, as yarns without plasma treatment and with plasma treatment with a ratio of water and carbon ink concentrations of 1:1 and 2:1. The results of the electrical conductivity with plasma treatment and the concentration of carbon ink and water of 1:1 and 1:2 were 69005 (Ωm)-1 and 50144.25 (Ωm)-1, respectively, while the results of the electrical conductivity for threads with concentrations of carbon ink and water of 1:1 and 1:2 without plasma treatment were 18197.64 (Ωm)‑1 and 8873.54 (Ωm)-1, respectively. The results showed that the concentration of carbon ink and water and plasma treatment affected the conductive value of the yarn. The results also showed that the presence of plasma pre-treatment improved the coating process of conductive ink on the yarn.